Medusa - Burton, Jessie, 1982- (Bloomsbury YA, Bloomsbury Publishing Inc., part of Bloomsbury Publsihing Plc, 2022)
Exiled to a far-flung island, Medusa has little company except for the snakes adorning her head instead of hair until a beautiful boy named Perseus arrives, disrupting her lonely existence and unleashing desire, love, and betrayal.